Additive manufacturing - Bandyopadhyay, Amit, 1967-; Bose, Susmita (CRC Press, 2020)
The field of additive manufacturing is growing dynamically as the interest is persisting from manufacturing sector, including other sectors as well. Conceptually, additive manufacturing is a way to build parts without using any part-specific tooling or dies from the computer-aided design (CAD) file of the part. Second edition of Additive Manufacturing highlights the latest advancements in the field, taking an application oriented approach. It includes new material on traditional polymer based rapid prototyping technologies, additive manufacturing of metals and alloys including related design issues. Each chapter comes with suggested reading, questions for instructors and PowerPoint slides.